On groups factorized by finitely many subgroups - Landolfi Т. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove that every group factorizable into a product of finitely many pairwise permutable central-by-finite minimax subgroups is a soluble-by-finite group.